Equality and equity in education: tensions and transitions - De la Cruz Flores, Gabriela (2017)
In today’s society knowledge and economic growth are interdependent. Becauseof this, the concept of equity has gained momentum in educational debate. Thispaper have the purpose to contribute to this debate. The tensions and transitionsaround educational equity in the context of Latin America are discussed. Therelationship between equality and equity is analyzed. the complementaritybetween scholar equity and systemic equity is discussed; the concept of equity showing it as dynamic and changing in accordance with social and educational contexts is examined; it is argued on the need for equity in transit from primary education to senior high school. Finally, the passage of equity focused exclusively on coverage towards equity in educational quality is examined.